O dilema extensão universitária - Hunger, Dagmar [UNESP]; Rossi, Fernanda [UNESP]; Pereira, Juliana Martins; Nozaki, Joice Mayumi (Faculdade de Educação da Universidade Federal de Minas Gerais, 2014)
This study aimed to examine on how a group of professors conceptualizes University Extension Programs, better yet, on how this function on daily teaching practices is evaluated. The empirical material (structured interviews) was discussed based on the theory of Norbert Elias, by interpreting the compulsive specific power in the university set. It was found that respondents are based on groups of intellectuals who compete and fall behind among teaching functions, research and extension programs and thus measure their competence. At times they pursuit from the research strength their academic recognition, hence, they criticize the extension program without getting involved with research, or yet, they are in favor to extension program by proposing modification of the surrounding world through it. Altogether the extension program will ensure a better professional training. It was concluded that the University Extension program is an academic dilemma, or rather, there is evidence of attempted resolutions, but still not a single one was fully acceptable by the entire academic community.

Objetivou-se analisar como um grupo de professores universitários conceitua a Extensão Universitária, ou melhor, como avalia tal função no cotidiano das ações docentes. Discutiu-se o material empírico (entrevistas) com base na teoria de Norbert Elias, interpretando-se as forças específicas compulsivas no jogo universitário. Constatou-se que os professores entrevistados se baseiam em grupos de intelectuais que jogam e se perdem entre as funções do ensino, da pesquisa e da extensão, e assim medem as suas forças. Ora buscam na força da pesquisa o reconhecimento acadêmico ou, então, criticam a Extensão sem envolvimento com pesquisa ou, ainda, são favoráveis à Extensão e propõem a modificação do mundo circundante por intermédio da Extensão, defendendo-a por garantir melhor formação profissional. Concluiu-se que a Extensão Universitária é um dilema acadêmico, ou melhor, evidenciam-se tentativas de resoluções, mas ainda nenhuma delas plenamente aceitável pela totalidade da comunidade acadêmica.
University extension dilemma
Keywords: universidade; extensão; universitária; docentes; university; university extension programs; professors